The relative importance of strength and power qualities to vertical jump height of elite beach volleyball players during the counter-movement and squat jump - Riggs, M. P.; Sheppard, J. M. (Journal of Human Sport & Exercise, 2009)
Despite the inclusion of beach volleyball as an Olympic discipline with a fully professional world tour, little research has been published that has examined the physical qualities of internationally competitive athletes. Thirty international-standard beach volleyball athletes (14 male, 16 female) performed countermovement jumps (CMJ) and squat jumps (SJ) on a force platform. Ground reaction force (GRF) was collected from three SJ separated by 30 seconds passive rest, followed by three CMJ separated by 30 seconds passive rest. Significant differences (P0.01) between male and female groups were found for all measured GRF characteristics of the SJ and CMJ, with the exception of peak rate of force development, relative peak force, power and relative average power for the CMJ test. For centre of mass displacement (jump height) the male mean was 8.33cm greater than the female mean. The strongest positive correlations with female jump height were SJ: Relative Peak Power (r=0.90); CMJ: Relative Average Power (r=0.67) The strongest positive correlations with male jump height were SJ: Relative Peak Power (r=0.94); Male CMJ: Relative Peak Power (r=0.83). No significant difference (P0.05) was shown between male and female stretch shortening cycle (SSC) performance as examined by a prestretch augmentation and eccentric utilisation ratios for jump height and peak power. The findings of this study suggest that relative peak and average power outputs are factors highly associated with vertical jump height in elite male and female beach volleyball players.